Pengembangan KOPER (Kotak Permainan) untuk Materi Klasifikasi Makhluk Hidup di SMP - Dio Alfando; Darmanella Dian Eka Wati (Pendidikan Biologi FKIP UMMY, 2019)
Fun learning can increase students' learning desires. The game allows active participation both between students and teachers and vice versa, also between students and other students. Therefore we want to develop creativity and innovation talent to develop new games that can make students able to play while learning with the title